Nanoporous silver microstructure for single particle surface-enhanced Raman scattering spectroscopy. Issue 2 (3rd December 2014) - Wongravee, Kanet; Gatemala, Harnchana; Thammacharoen, Chuchaat; Ekgasit, Sanong; Vantasin, Sanpon; Tanabe, Ichiro; Ozaki, Yukihiro
Abstract : Nanoporous silver microstructures were successfully fabricated from hexapod AgCl microstructures via a galvanic replacement reaction to be used as an easy handling and reusable SERS substrate. Abstract : The potential of a nanoporous Ag microstructure (np-AgMs) for use as a single particle for surface-enhanced Raman scattering spectroscopy (SERS), with the added advantages of being easy to manipulate and reusable, was successfully demonstrated. The np-AgMs with interconnected pore and controllable pore size were fabricated from symmetric hexapod AgCl via a galvanic replacement reaction in NaCl solution with zinc (Zn) as the sacrificed metal. The clean surface of np-AgMs enables rapid surface functionalization with easy handling and sample preparation as no particle aggregation occurs. The SERS acquisition spots on the np-AgMs can be visually selected using a normal Raman microscope. SERS spectra of p -aminothiophenol (PATP) with a concentration range of 10 −8 –10 −3 M can be achieved. The position-dependent enhancement of np-AgMs was expendably evaluated. The signal-position correlation was confirmed by electric filed enhancement obtained from Finite-difference time-domain (FDTD) calculation. In addition, the highly stable substrate showed insignificant loss of the enhanced Raman signal after several cycles of chemical re-generation. Finally, the potential application of np-AgMs in label-free detection of biomolecules including hemoprotein, protein without chromophore and DNA strains at low concentration of 500 μg mL −1 was demonstrated.